Organic food processing: a framework for concept, starting definitions and evaluation. (13th February 2014) - Kahl, Johannes; Alborzi, Farnaz; Beck, Alexander; Bügel, Susanne; Busscher, Nicolaas; Geier, Uwe; Matt, Darja; Meischner, Tabea; Paoletti, Flavio; Pehme, Sirli; Ploeger, Angelika; Rembiałkowska, Ewa; et al.
Abstract In 2007 EU Regulation (EC) 834/2007 introduced principles and criteria for organic food processing. These regulations have been analysed and discussed in several scientific publications and research project reports. Recently, organic food quality was described by principles, aspects and criteria. These principles from organic agriculture were verified and adapted for organic food processing. Different levels for evaluation were suggested. In another document, underlying paradigms and consumer perception of organic food were reviewed against functional food, resulting in identifying integral product identity as the underlying paradigm and a holistic quality view connected to naturalness as consumers' perception of organic food quality. In a European study, the quality concept was applied to the organic food chain, resulting in a problem, namely that clear principles and related criteria were missing to evaluate processing methods. Therefore the goal of this paper is to describe and discuss the topic of organic food processing to make it operational. A conceptual background for organic food processing is given by verifying the underlying paradigms and principles of organic farming and organic food as well as on organic processing. The proposed definition connects organic processing to related systems such as minimal, sustainable and careful, gentle processing, and describes clear principles and related criteria. Based on food examples, such as milk with different heat treatments, the concept and definitions were verified. Organic processing can be defined by clear paradigms and principles and evaluated according criteria from a multidimensional approach. Further work has to be done on developing indicators and parameters for assessment of organic food quality. © 2013 Society of Chemical Industry